MRI provision for patients with cardiac implantable electronic devices: understanding the real-world administrative requirements of service delivery. (14th October 2021) - Dowsing, B; Cash, L; Webb, E; Moon, J C; Manisty, C H; Bhuva, A N
Abstract: Introduction: Patients with cardiac implantable electronic devices (CIEDs) should have access to Magnetic Resonance Imaging (MRI) but are less likely to be referred and hospitals lack provision. A major barrier to service delivery is the administrative demand required to obtain accurate CIED details prior to scheduling. We aimed to understand the administrative requirements of a high-volume Cardiac Device-MRI service to inform the design of an electronic referrals platform that can facilitate workflow. Methods: Single centre retrospective audit of a high-volume Cardiac Device-MRI service in a tertiary unit in the UK. Six months of referrals were reviewed for patient and CIED details and barriers met. Referrals were stratified by source, indication, MR-Conditional labelling and referrer. Results: Administrative barriers were reviewed for 116 patients with CIEDs referred for MRI (48% cardiac, 52% non-cardiac) between September 2020 and March 2021 (Table 1). Referrers were 47% cardiologists and 53% other specialties. Referral to scan time was 15 days (interquartile range, 8–32). There were no scan-related complications. 34% of referrals contained complete CIED details and 30% stated the MR labelling of the CIED. None incorrectly labelled a CIED as MR-Conditional, but 8% incorrectly labelled as non-MR Conditional. 7 additional days were required to obtain complete CIED details where not provided (involving information requests from two device clinics in 27%), 10% had delays over 2 weeks (maximum 145 days). 35% required 3 or more repeat discussions with referrers after initial referral. Obtaining CIED information for external referrals required 17 days (11–42), compared to 14 (6–35) days for internal referrals (p=0.25). Patients with non-MR Conditional CIEDs required on average 14 days longer to obtain complete referral details than patients with MR-Conditional CIEDs. Even when referrers were aware of non-MR Conditional labelling and received information on risk, 41% required further discussion between patient and referrer regarding risks and benefits of MRI scanning. For cancer referrals, obtaining correct details took 1 day longer than other referrals (p=0.074) and required 2 extra emails to maintain provision within the national time-to-treatment target of 62 days. Missing data was similarly present in referrals from Cardiologists and non-Cardiologists (59% versus 61% respectively), but non-Cardiologists recorded more incorrect CIED details (8% vs 0%). Conclusions: Referral for MRI in patients with CIEDs demands significant administrative input to obtain correct device information, leading to delays. These delays are greater for patients with non-MR conditional CIEDs, and data provided is often incorrect or incomplete. This may explain why some patients are not referred for MRI. An online referrals platform has been developed to streamline this process, initially deployed through a network of 60 centres registered in the UK. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): This work is supported by British Heart Foundation Innovations funding (HFHF_016).